Introducing Leather in Wearable Triboelectric Generators - Aristeidis Repoulias; Ilda Kazani; Sotiria F Galata; Sindi Cela; Savvas Vassiliadis (Textile & Leather Review, 2024)
Leather is a well-known material with a wide range of applications in clothing, footwear, protection, accessories and furnishing. Further on it is reported in only a few triboelectric series tables, as a material which has an intensive tendency to become positive. In the hereby study, its triboelectric potentials are examined to be used as part of a triboelectric generator which would be part of clothing. Natural leather from cows and sheep was used. Samples of 25 cm2 area were cut and examined together with Polytetrafluoroethylene (PTFE) material, using a prototype measuring triboelectric generator device under a force of 0.5 N. The highest Vpp values were given by the front (grain) side of cow and sheep thin samples, reaching a mean Vpp of 1293 and 1233 mV respectively. In all the tests, the front side of the samples performed better than their back (flesh) as a triboelectric surface. Additionally, the thin samples performed better than the thick ones and the less stiff samples performed better than the stiff ones. The outcoming voltages seem promising in comparison to other ordinary natural materials previously studied. The results point to the potential of leather usage in wearable triboelectric generators.